THE ISSUE OF SYNCRETISM IN THE SYSTEM OF MINOR MEMBERS OF A SENTENCE - Грозян, Ніна (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
At present the boundaries of the traditionally isolated sentence members do not show the whole variety of syntactic categories and semantic-syntactic components. The inclusion of syncretic sentence members into the traditional classification is explained by the intention to avoid unique and categorical nature as to the classification of syntactic units, the desire to secure from the 29 difficulties of their typologization. The relevance of the topic of the research is conditioned by the necessity to study syncretic formations in the system of sentence members. The unification of the terms which denote syncretic minor sentence members, their classification characteristics and peculiarities of typology requires further research. The purpose of the paper is to analyze syncretic minor sentence members in the context of forming terminology to denote syncretic units, to define their classification characteristics and peculiar aspects of typology. Results. The paper covers the issue of syncretism in the system of minor sentence members. The tools, which denote syncretic units and are based on traditionally isolated sentence members, are described. This approach results from the practical consideration and the need to improve a traditional system of minor members of a sentence, having isolated the syncretic units. Classification characteristics of syncretic minor sentence members, which are based on their correlation with formal-syntactic, semantic-syntactic and communicative correspondents, were identified. The kinds of syncretic minor members of a sentence were differentiated. Two structural types were classified by the nature of syntactic connection: syncretic minor sentence members with a single and binary connection. Within the first type the following was differentiated: adverbial attributes, adverbial objects, attributive objects and adverbial-objective attributes. Duplexes, adverbial attributes and adverbial-objective attributes were differentiated within syncretic minor sentence members with a binary connection. It has been found out that the connection with a name results in an attributive meaning, and that with a verb results in an adverbial (or objective) meaning. Originality. The originality of the research consists in the unification of the terms to nominate syncretic minor members of a sentence; to find out their qualification characteristics and to ground the typology which relies on a traditional system of sentence members. Conclusion. The conclusion has been made that it is not possible to give a unique classification of minor sentence members according to their traditional description. The introduction of a concept about syncretic sentence members will help avoid difficulties. The suggested terminological tools of denoting syncretic units rely on traditionally isolated sentence members. Classification characteristics of syncretic minor sentence members are based on their correlations with formal-syntactic, semanticsyntactic and communicative corresponding units. Two structural types were differentiated by the nature of a syntactic connection: syncretic minor sentence members with a single and binary connection. Within the first type the following was differentiated: adverbial attributes, adverbial objects, attributive objects and adverbial-objective attributes. Duplexes, adverbial attributes and adverbial-objective attributes were differentiated within syncretic minor sentence members with a binary connection. We see the perspective of further research in the characteristics of the kinds of syncretic minor members of a sentence.